Dengue: Profile and incidence of notifiable disease cases in a region of western Paraná in the year 2022 (Research, Society and Development, 2023)
The year 2022 was marked by a dengue epidemic in the tenth health region of the state of Paraná, which reported 21.683 cases to the Ministry of Health. The work in question deals with the epidemiological profile and the number of cases notified in this region, which covers 25 municipalities and aims to succinctly address reliable data about dengue arbovirus in the 10th health region of the State of Paraná. The data was taken from the Notifiable Diseases Information System (in Portuguese, Sistema de informação de agravos de notificação - SINAN), which includes the DataSus/TabNet platform. The data was tabulated in an Excel spreadsheet using percentage calculations and the presentation of graphs and tables. The study analyzed the particularities of gender, age group, race, schooling, pregnancy, serology, confirmation criteria, final classification of the disease, month of symptoms and evolution in the year 2022, with emphasis on cases with the need for hospitalization. In addition to the comparison with the data obtained in 2019, it can be seen that the epidemiological profile of the disease undergoes variations, albeit slight ones, and that the number of deaths predominantly affects the extremes of age, especially when it comes to the presence of comorbidities in the elderly. The conclusion is that the dengue arbovirus can have endemic and epidemic cycles, which can overload the health system, especially during the Brazilian summer months, which are more favorable for the development and hatching of larvae.